2015
DOI: 10.1080/19768354.2015.1060261
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cell growth and down-regulation of telomerase activity by amygdalin in human cancer cell lines

Abstract: The purpose of this study was to examine the effect of amygdalin on cell growth and telomerase activity in human cancer and MRC-5 fibroblast cell lines. The level of β-glucosidase activity for releasing cyanide was significantly (P < .05) higher in cancer cell lines (A-549, MDA-MB-231, MCF-7 and U87-MG) than in MRC-5 fibroblasts. Growth rate of cancer cells was apparently inhibited in concentrations above 10 mg/ml amygdalin with senescent-like abnormal morphology. Whereas the effects were absent or marginally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Krebs (1940) discovered that Beta-glucosidase splits vitamin B17 into toxic cyanide ions Results ensured that amygdalin extracted from apricot kernels had appreciable anticancer activity towards colorectal (HT-29) cancer cell line with IC50 valued 30 µM. Our results were in accordance with Moon et al (2015) who concluded that amygdalin inhibited cell growth and down-regulation of telomerase activity by increasing ßglucosidase activity. Amygdalin had antitumor by inducing apoptosis and regulating immune function Shi et al (2019).…”
Section: Anticancer Activity Of Apricot Amygdalinsupporting
confidence: 86%
“…Krebs (1940) discovered that Beta-glucosidase splits vitamin B17 into toxic cyanide ions Results ensured that amygdalin extracted from apricot kernels had appreciable anticancer activity towards colorectal (HT-29) cancer cell line with IC50 valued 30 µM. Our results were in accordance with Moon et al (2015) who concluded that amygdalin inhibited cell growth and down-regulation of telomerase activity by increasing ßglucosidase activity. Amygdalin had antitumor by inducing apoptosis and regulating immune function Shi et al (2019).…”
Section: Anticancer Activity Of Apricot Amygdalinsupporting
confidence: 86%
“…Even though the present study has not investigated the cytotoxic effects, such as the proliferation & apoptosis in normal cell lines after prolonged exposure at 1 μM SMA concentration, we have assumed that the less cellular cytotoxic effects on cell proliferation by treatment of SMA are exhibited in the normal cell lines than those of cancer cell lines when compared with our earlier results, and probably that SMA could be considered as a selective anti-tumor drug for chemotherapy treatment. The selective cytotoxicity-inducing compounds could be more effective as anti-tumor drugs for therapeutic treatment of cancer cells with less cytotoxic effects in the normal cell lines than cancer cells (Jeon et al 2011a ; Moon et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The β-galactosidase enzyme is a glycoside hydrolase that break glycosidic bonds. The endogenous lysosomal β-galactosidase protein is generally overexpressed in the senescent cells, and thus cellular aging and senescence is measured by its activity (Lee et al 2006 ; Moon et al 2015 ). The treatment of SMA has shown higher activity of senescence-associated-β-galactosidase in the present study, implying that cellular senescence was proceeding.…”
Section: Discussionmentioning
confidence: 99%
“…In recent study the effect of amygdalin on cell growth and telomerase activity in human cancer and MRC-5 fibroblast cell lines investigated and it was found that above 10 mg/ml concentration of amygdalin inhibited the growth rate of cancer cells. Also, their research indicated that telomerase activity significantly down-regulated in amygdalintreated cancer cell lines (A-549, MDA-MB-231, MCF-7, and U87-MG) with the decreased expression of telomerase reverse transcriptase (TERT) and telomerase RNA component (TERC) compared with control cancer cells (MOON et al, 2015). Their findings confirmed the results of the present study on effects of amygdalin on inhibition of MCF-7 growth and leading to the mortality and prevention of the spreading of these cancer cell lines after treating by this herbal compound.…”
Section: Verification Of Cdna Synthesismentioning
confidence: 99%